(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
Multiple fractional derivatives enrich the dynamic properties of fractional differential equations. This paper concerns with neutral fractional functional differential equations with two Caputo fractional derivatives. By using the fixed point methods with the fractional integral inequalities, the existence results and controllability of the equations are considered in the cases of finite delay and infinite delay, respectively. An example is given to illustrate the main results.